2017
DOI: 10.1037/xge0000269
|View full text |Cite
|
Sign up to set email alerts
|

Motor experience influences object knowledge.

Abstract: An object’s perceived readiness-for-action (e.g., its size, the degree of rotation from its canonical position, or the user’s viewpoint) can influence semantic knowledge retrieval. Yet, the organization of object knowledge may also be affected by body-specific sensorimotor experiences. Here, we investigated whether people’s history of performing motor actions with their hands influences the knowledge they store and retrieve about graspable objects. We compared object representations between healthy right- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 111 publications
0
19
3
1
Order By: Relevance
“…In so doing, we tried to increase the attention paid to the vertical axis while bringing to a minimum the salience of the horizontal dimension. Given that certain aspects of our knowledge and representation of objects seem to be determined by motor experience and the canonical position of objects, that is, the prototypical way we interact with them (Chrysikou, Casasanto, & Thompson-Schill, 2017), we hypothesized that a change in the conventional position of the response pad and the customary way participants use their hand to interact with it should attract attention to the new body-object spatial configuration enhancing the salience of the vertical axis and making it the only relevant spatial frame for the task. In this context, we predicted that the conceptual projection of valence onto vertical space would be favored provided that the response pattern that participants were assigned to was spatially congruent with the conceptual metaphors GOOD IS UP and BAD IS DOWN.…”
Section: Methodsmentioning
confidence: 99%
“…In so doing, we tried to increase the attention paid to the vertical axis while bringing to a minimum the salience of the horizontal dimension. Given that certain aspects of our knowledge and representation of objects seem to be determined by motor experience and the canonical position of objects, that is, the prototypical way we interact with them (Chrysikou, Casasanto, & Thompson-Schill, 2017), we hypothesized that a change in the conventional position of the response pad and the customary way participants use their hand to interact with it should attract attention to the new body-object spatial configuration enhancing the salience of the vertical axis and making it the only relevant spatial frame for the task. In this context, we predicted that the conceptual projection of valence onto vertical space would be favored provided that the response pattern that participants were assigned to was spatially congruent with the conceptual metaphors GOOD IS UP and BAD IS DOWN.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, compared to low-graspability objects, high-graspability objects were named faster (Guérard et al, 2015; Lorenzoni et al, 2018). Our explanation for the null result is that the effect of manipulation on object processing is mediated by manipulation experience, as evidence has indicated that the causal role of action information in objects' conceptual representations is established through manual experience (Yee et al, 2013; Chrysikou et al, 2017). The distribution statistics of manipulation experience, nevertheless, show that our participants had little experience in acting upon most of the objects in our dataset in spite of their high scores on manipulability.…”
Section: Discussionmentioning
confidence: 79%
“…The effect of manipulability on object recognition, however, is found to be mediated by the amount of manipulation experience associated with that object. The more experience we have in manipulating the object, the heavier role manual action plays in object representation (Yee et al, 2013; Chrysikou et al, 2017). Thus, we decided to include manipulation experience as another new variable in our image set.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, given that even as adults, the input that we receive changes as our experiences change in both the long and short term (e.g. via changes in our cultural, physical, or bodily environments, or in our knowledge or goals) our concepts should continue to change as well (for recent evidence of conceptual evolution due to changes in the body and knowledge, respectively, see Chrysikou, Casasanto, & Thompson-Schill, 2017;and Clarke, Pell, Ranganath, & Tyler, 2016; for review see Yee & Thompson-Schill, 2016).…”
mentioning
confidence: 99%